2014
DOI: 10.1016/j.neuron.2014.10.048
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Micro-organization of Grid Cells Revealed by Cellular-Resolution Imaging

Abstract: Summary Establishing how grid cells are anatomically arranged, on a microscopic scale, in relation to their firing patterns in the environment would facilitate a greater micro-circuit level understanding of the brain’s representation of space. However, all previous grid cell recordings used electrode techniques that provide limited descriptions of fine-scale organization. We therefore developed a technique for cellular-resolution functional imaging of medial entorhinal cortex (MEC) neurons in mice navigating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
168
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(185 citation statements)
references
References 53 publications
10
168
0
4
Order By: Relevance
“…Cell pairs <35 μm apart, displayed a significant correlation but not separable from correlations from common neuropil or activity bleed-over in the imaging technique (Dombeck et al 2010). Imaging of grid cells using similar methods has recently confirmed that grid phase is organized non-topographically at the macroscopic level, but larger-than-expected correlations were reported for cells that were nearest neighbors (Heys et al 2014).…”
Section: Topography In Parahippocampal Systemsmentioning
confidence: 94%
See 1 more Smart Citation
“…Cell pairs <35 μm apart, displayed a significant correlation but not separable from correlations from common neuropil or activity bleed-over in the imaging technique (Dombeck et al 2010). Imaging of grid cells using similar methods has recently confirmed that grid phase is organized non-topographically at the macroscopic level, but larger-than-expected correlations were reported for cells that were nearest neighbors (Heys et al 2014).…”
Section: Topography In Parahippocampal Systemsmentioning
confidence: 94%
“…It should be kept in mind, however, that the identification of explicit representations with linearly separable ones is a working hypothesis that remains under-investigated. More generally, it is particularly difficult to determine whether and how brain responses play a causal role in behavior and subjective perception (see, e.g., Rangarajan et al 2014). Beyond decoding analyses, this ambiguity is in fact intrinsic to any non-causal brain-behavior correlation method.…”
Section: Advantages Of Multivariate Decoding Methodsmentioning
confidence: 99%
“…Might such connectivity between clonally related cells underlie a possible preferential coupling between MEC cells with similar spatial or directional tuning, in the same way that cells from the same clone exhibit similarities in orientation preferences (and possibly preferential coupling) in the visual cortex 268,269 ? Does the young MEC have a topographically arranged teaching layer, with connections between clonally related cells, that during early postnatal development gives way to the largely nontopographical 9,270 grid cell network of the adult MEC (Fig. 8 of ref. 91)?…”
Section: Development Of Spatial Network Architecturesmentioning
confidence: 99%
“…Последнее подразумевает, что функция корреляции между импульсной активностью двух клеток решетки в зависимости от физического расстояния между этими нейронами имеет форму мексиканской шляпы, т.е. нейроны, расположенные рядом, разряжаются в одинаковые моменты времени, а импульсные последовательности нейронов, расположенных на среднем расстоянии, анти-коррелированы [31,49].…”
Section: клетки решеткиunclassified
“…При введении в модель дополнений, например, ритмического входа [75], можно получить эффект фазовой прецессии, однако в чем заключается роль этого явления, модель не описывает. С другой стороны, в последнее время аттракторные модели получили значительную поддержку в виде работ, показывающих пространственную и функциональную кластеризацию нейронов энторинальной коры [31,49].…”
Section: фаза импульсаunclassified